Influence of wind speed on the performance of photovoltaic panel - Leow Wai Zhe; Y.M. Irwan; M. Irwanto; A.R. Amelia; I. Safwati (Institute of Advanced Engineering and Science, 2019)
The aim of this project is to investigate the performance of photovoltaic (PV) panel influence by wind speed in Kangar, Perlis, Malaysia. A low conversion energy efficiency of the PV panel is the major problem of a PV application system. The PV panel is absorbed solar irradiance minor converted into electrical energy, and the rest is converted into heat energy. Therefore, the heat energy generated by the PV panel is increased in its operating temperature. However, PV panel is necessary to operate them at the low operating temperatures to keep the PV panel electrical efficiency at an acceptable level. In this experiment, one unit of the PV panel was limited wind flow over its surface and the other one PV panel was operated in the normal condition. The operating temperature of the PV panel with wind speed is less than the PV panel without wind speed. This is due to wind flow over the surface of the PV panel can enhance heat extraction from the PV panel. Hence, PV panel with wind speed can generate a higher output power than that without wind speed. This improvement output performance of PV panel will have an important contribution to PV application systems.